REDUCED- VS STANDARD-INTENSITY IV THROMBOLYSIS IN ACUTE ISCHEMIC STROKE AMONG ADULTS ≥ 80 YEARS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Dr Taarif Hussain MD; Dr Shahnila Ali; Dr Hasan Javed; Dr Muhammad Umar Farooq; Dr Zulekha Ilyas; Dr Syed Muhammad Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Optimal thrombolytic dosing for very elderly patients with acute ischemic stroke (AIS) remains uncertain. While standard-dose alteplase (0.9 mg/kg) is globally established, low-dose regimens (0.6 mg/kg) are often used in Asia to reduce hemorrhagic risk. Tenecteplase (TNK), particularly at 0.25 mg/kg, is emerging as a potential alternative, but evidence in patients aged ≥ 80 years is limited.1–6 Methods: We conducted a systematic review and meta-analysis in accordance with PRISMA guidelines (databases: PubMed, Embase, CENTRAL, Web of Science, ClinicalTrials.gov, WHO ICTRP; 1995–Aug 2025). Eligible studies included randomized controlled trials (RCTs) and comparative cohorts of AIS patients aged ≥ 80 years treated with intravenous alteplase or Tenecteplase. Primary outcomes were functional independence (modified Rankin Scale [mRS] 0–2 at 90 days) and symptomatic intracranial hemorrhage (sICH). Risk of bias was assessed using RoB 2 for RCTs and ROBINS-I for cohorts. Random-effects meta-analysis was performed where subgroup data were available; otherwise, results were narratively synthesized. Results: From 524 records, 62 full texts were reviewed, and 7 studies were included. Only one study provided quantitative ≥ 80-specific data.3 In a multicenter cohort of octogenarians, standard-dose alteplase achieved higher rates of functional independence than low-dose (34.8% vs 22.2%; RR 0.64; 95% CI, 0.42–0.97) with comparable sICH rates. The ENCHANTED trial demonstrated reduced sICH with low-dose alteplase but failed to confirm non-inferiority for efficacy, with no interaction by age ≥ 80.1,2 Trials of Tenecteplase indicated that 0.40 mg/kg conferred no clinical benefit and increased bleeding risk,4 whereas 0.25 mg/kg appeared non-inferior to standard-dose alteplase and safer than higher TNK dosing.5,6,8–10 Conclusions: For AIS patients aged ≥ 80 years, standard-dose alteplase provides superior functional outcomes compared with low-dose, though with persistent bleeding concerns. Tenecteplase at 0.25 mg/kg represents a promising alternative, balancing efficacy, safety, and practical advantages.7,9–14 However, evidence remains limited, with few ≥80-specific RCTs and heterogeneity in sICH definitions. Dedicated age-specific trials, pooled IPD meta-analyses, and large- scale registries are urgently needed to guide thrombolysis decisions in this high- risk population.